2014
DOI: 10.1289/ehp.1306758
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Weight Gain and Exposure of Newborns to Persistent Organic Pollutants

Abstract: Background: Exposure to persistent organic pollutants (POPs) during fetal development can increase the risk of adverse health effects during childhood. Maternal characteristics and physiological changes during gestation, such as gestational weight gain (GWG), may have an influence in the overall burden of POPs in neonates. However, the associations between GWG and POP concentrations are still not well established.Objective: We examined the association of GWG with cord serum POPs concentrations after adjusting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Vizcaino et al [33] have suggested an association between prenatal exposure to POPs and inadequate gestational weight gain. While few reports on the possible effects of POP exposure on fetal growth have been published to date, some evidence suggests that prenatal exposure to these compounds could be associated with disturbed hormone levels during pregnancy [34-36].…”
Section: Discussionmentioning
confidence: 99%
“…Vizcaino et al [33] have suggested an association between prenatal exposure to POPs and inadequate gestational weight gain. While few reports on the possible effects of POP exposure on fetal growth have been published to date, some evidence suggests that prenatal exposure to these compounds could be associated with disturbed hormone levels during pregnancy [34-36].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal gestational weight gain (GWG) will dilute the EDC concentrations in maternal blood and is also overall positively associated with birth weight of the child, and may therefore be a confounder of the associations between EDCs and birth weight (Verner et al, 2013). Associations between GWG and cord serum concentrations of ΣPCBs, 4,4′-DDE and HCB have been reported (Vizcaino et al, 2014). We evaluated whether GWG confounded the associations of the EDCs with SGA in the subset of the pooled data having information on GWG (Table 1).…”
Section: Confounders and Risk Factorsmentioning
confidence: 99%
“…Fish consumption has been associated to human accumulation of mercury (Hg) and organochlorine pesticides (Llop et al, 2010;Gascon et al, 2012Gascon et al, , 2013Garí et al, 2013;Vizcaino et al, 2014;Costa et al, 2016;Bravo et al, 2017). Despite their different origin and structure, OCs and Hg share common properties such as (I) strong chemical stability and environmental persistence, (II) bioconcentration in living organisms and biomagnification through the food chain due to their hydrophobic character and (III) toxicity for humans and wild animals.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the production and use of OCs and Hg has been restricted and/or banned in many countries. However, these contaminants are still found in the environmental compartments (Arellano et al, 2011;Lamborg et al, 2014), foodstuff (Martí-Cid et al, 2010;Olmedo et al, 2013) and human tissues (Vizcaino et al, 2014;Garí et al, 2013).…”
Section: Introductionmentioning
confidence: 99%